2015
DOI: 10.1021/acs.jpcb.5b04528
|View full text |Cite
|
Sign up to set email alerts
|

Mapping Protein Conformational Landscapes under Strongly Native Conditions with Hydrogen Exchange Mass Spectrometry

Abstract: The thermodynamic stability and kinetic barriers separating protein conformations under native conditions are critical for proper protein function and understanding dysfunction in diseases of protein conformation. Traditional methods to probe protein unfolding and folding employ denaturants and highly non-native conditions, which may destabilize intermediate species or cause irreversible aggregation especially at the high protein concentrations typically required. Hydrogen exchange (HX) is ideal for detecting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…MS data were analyzed by discrete fitting as well as by global fitting (Supporting Information), assuming that the mass distributions of all the species populated during refolding could be described as Gaussian distributions. Analysis of pulsed HX-MS data by fitting mass profiles to the sum of Gaussian distributions, each arising from HX into a distinct protein conformation, is an effective way to delineate the mechanism of exchange and structural transitions . The mass profiles obtained from the HX studies for the intact protein and for the different segments of the protein were analyzed as the sum of two, three, or four Gaussian distributions using eq : where a represents the area under each Gaussian distribution and b and c represent the values of the peak m / z position and the width, respectively, of each of n Gaussian distributions.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…MS data were analyzed by discrete fitting as well as by global fitting (Supporting Information), assuming that the mass distributions of all the species populated during refolding could be described as Gaussian distributions. Analysis of pulsed HX-MS data by fitting mass profiles to the sum of Gaussian distributions, each arising from HX into a distinct protein conformation, is an effective way to delineate the mechanism of exchange and structural transitions . The mass profiles obtained from the HX studies for the intact protein and for the different segments of the protein were analyzed as the sum of two, three, or four Gaussian distributions using eq : where a represents the area under each Gaussian distribution and b and c represent the values of the peak m / z position and the width, respectively, of each of n Gaussian distributions.…”
Section: Methodsmentioning
confidence: 99%
“…Analysis of pulsed HX-MS data by fitting mass profiles to the sum of Gaussian distributions, each arising from HX into a distinct protein conformation, is an effective way to delineate the mechanism of exchange and structural transitions. 55 The mass profiles obtained from the HX studies for the intact protein and for the different segments of the protein were analyzed as the sum of two, three, or four Gaussian distributions using eq 1:…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…In fact, we demonstrated that a simple analytical model for the exchange of a 2-state protein undergoing HXMS due to global unfolding came very close to replicating the apparent 3-state experimental HXMS behavior for the amyloidogenic protein β2M under nearnative equilibrium conditions. 27 My computational undergraduates (mostly those who are majoring in Mathematics or Computer Science in addition to Chemistry or Biochemistry and Biophysics) have built a numerical simulations approach to fit complex HXMS time course data and clearly distinguish whether the spectra arise from a 2-state (no intermediate) or 3-state (possesses a folding intermediate) folder. My wet-lab students have been using model proteins to develop the experimental NHXMS workflow.…”
Section: Landscape Exploration As a Developing Protein Scientistmentioning
confidence: 99%
“…Analysis was carried out by plot-ting observed mean mass as a function of time of exchange, assuming that exchange is occurring under the EX2 regime, although peak width analysis suggests that the slowest phase of exchange at pH 7 could be under the EXX regime (Fig. S8 b) (67,68) because it shows significant increase in peak width as a function of time. The exchange at pH 4 does not show such increase in peak width, suggesting an EX2 exchange mechanism.…”
Section: Ccdb_4 Has Lower Local Stability Than the Native Statementioning
confidence: 99%